Intraduodenal levodopa-carbidopa intestinal gel infusion improves both motor performance and quality of life in advanced Parkinson's disease. (March 2016) - Chang, Florence C.F.; Kwan, Vu; van der Poorten, David; Mahant, Neil; Wolfe, Nigel; Ha, Ainhi D.; Griffith, Jane M.; Tsui, David; Kim, Samuel D.; Fung, Victor S.C.
Abstract: We report the efficacy and adverse effect profile of intraduodenal levodopa-carbidopa intestinal gel (LCIG) infusion from patients treated in a single Australian movement disorder centre. We conducted an open-label, 12 month prospective study of treatment with LCIG in patients with advanced Parkinson's disease in a single tertiary referral hospital unit specialising in movement disorders. Patients with levodopa-responsive, advanced Parkinson's disease with motor fluctuations despite optimal pharmacological treatment were enrolled and underwent a 16 hour daily infusion of LCIG for 12 months. Fifteen participants completed the trial. The mean (±standard deviation) improvement in Unified Parkinson's Disease Rating Scale part III was 37 ± 11%, mean daily "off" period reduced from 6.3 ± 2 to 1.9 ± 2 hours, total daily "on" time increased from 10.2 ± 3 to 13.7 ± 2 hours, "on" period without dyskinesia increased from 4.5 ± 3 to 7.5 ± 5 hours, and 39-item Parkinson's Disease Questionnaire Summary Index score improved by 32.5 ± 35%. The most common adverse event was reversible peripheral neuropathy secondary to vitamin B12 ± B6 deficiency (40%), local tube problems (40%), and impulse control disorder (ICD) (27%). No patient had stoma bleeding or peritonitis. All patients with ICD had a past psychiatric diagnosis of depression with or without anxiety and a higher daily levodopa intake at 6 and 12 months of LCIG infusion. Intraduodenal LCIG improves motor performance, quality of life and daily "on" period. Prior to and during duodenal LCIG infusion, clinicians should monitor for peripheral neuropathy and vitamin B12 and B6 deficiency, as supplementation can reverse peripheral neuropathy. This trial is registered at Clinicaltrials.gov as CT00335153.